The Spatial Nature of Trust in Cosmopolitan Education - Hirose, Yuzo (Philosophical Inquiry in Education, 2023)
This paper investigates the core moment of cosmopolitan education by considering trust in education. Critical and postcolonial approaches recognize that dialogue plays a crucial role in cosmopolitan education. However, dialogue is not possible without sharing a fundamental platform. Trust could encourage us to construct this platform, and should thus be examined in an educational context. Previous studies on trust in education have mainly focused on the asymmetric relationship between educators and children, offering the impression that trust strengthens authoritarian order. However, in this paper I propose that trust in education needs to be recognized for containing a spatial and contextual nature, that is, a vertical trust between educators and children, and a horizontal trust especially between friends. Such spatial trust is based on trust in matters and therefore an open trust that embraces all matters in the world. This spatial trust could contribute to reinforcing cosmopolitan education, and furthermore, to formulating a post-anthropocentric cosmopolitan education.